Highly Stable Battery Pack via Insulated, Reinforced, Buckling‐Enabled Interconnect Array. Issue 43 (3rd July 2018) - Yin, Lu; Seo, Joon Kyo; Kurniawan, Jonas; Kumar, Rajan; Lv, Jian; Xie, Lingye; Liu, Xinyu; Xu, Sheng; Meng, Ying S.; Wang, Joseph
Abstract: This work describes a flexible and stretchable battery pack configuration that exhibits highly stable performance under large deformation up to 100% biaxial stretching. Using stress‐enduring printable inks and serpentine interconnects, the new screen‐printing route offers an attractive solution for converting rigid battery units into a flexible, stretchable energy storage device. Coin‐cell lithium ion batteries are thus assembled onto the island regions of a screen‐printed, buckling‐enabled, polymer‐reinforced interconnect "island‐bridge" array. Most of the strain on the new energy‐storage device is thus accommodated by the stress‐enduring serpentine structures, and the array is further reinforced by mechanically strong "backbone" layers. Battery pack arrays are assembled and tested under different deformation levels, demonstrating a highly stable performance (<2.5% change) under all test conditions. A light emitting diode band powered by the battery pack is tested on‐body, showing uninterrupted illumination regardless of any degrees of deformation. Moreover, battery‐powered devices that are ultrastable under large deformation can be easily fabricated by incorporating different electronics parts such as sensors or integrated circuits on the same platform. Such ability to apply traditionally rigid, bulky lithium ion batteries onto flexible and stretchable printed surfaces holds considerable promise for diverse wearable applications. Abstract : The fabrication of a flexible and stretchable Li‐ion battery pack using all‐printed buckling‐enabled island‐bridge configurated interconnections is demonstrated. The interconnection utilizes free‐standing serpentine structures for stretchability and is further reinforced with a "skeleton" layer for stability. The fabricated battery pack exhibits highly stable output for stretching deformation up to 100%.